2020
DOI: 10.1007/s10508-020-01843-3
|View full text |Cite
|
Sign up to set email alerts
|

Are Men Who Buy Sex Different from Men Who Do Not?: Exploring Sex Life Characteristics Based on a Randomized Population Survey in Sweden

Abstract: The buying and selling of sex is a topic of frequent discussion and a relevant public health issue. Studies of sex workers are available, while studies addressing the demand side of sex are scarce, especially based on robust population data. The current study provides national estimates of the prevalence of and factors associated with having paid for sex among men in Sweden. We used a randomized population-based survey on sexual and reproductive health and rights among ages 16–84 years, linked to nationwide re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Pascoal et al [8] indicated that, over the years, measures have been developed to evaluate different aspects of sexual satisfaction: 1) Those that emphasize the presence or lack of clinical indicators, such as the Golombok Rust Inventory of Sexual Satisfaction [23]; 2) Those that evaluate individual and relational dimensions, such as the New Sexual Satisfaction Scale [24]; 3) Those that emphasize the evaluation of the interpersonal component of sexuality, such as the Global Measure of Sexual Satisfaction [25]; 4) Those that assess gender-specific characteristics of sexuality such as the Sexual Satisfaction Scale for Women [26]; and 5) Those that assess relational dimensions and overall satisfaction with sexual life, such as the Index of Sexual Satisfaction [27]; or the Satisfaction with Sex Life Scale [28], among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pascoal et al [8] indicated that, over the years, measures have been developed to evaluate different aspects of sexual satisfaction: 1) Those that emphasize the presence or lack of clinical indicators, such as the Golombok Rust Inventory of Sexual Satisfaction [23]; 2) Those that evaluate individual and relational dimensions, such as the New Sexual Satisfaction Scale [24]; 3) Those that emphasize the evaluation of the interpersonal component of sexuality, such as the Global Measure of Sexual Satisfaction [25]; 4) Those that assess gender-specific characteristics of sexuality such as the Sexual Satisfaction Scale for Women [26]; and 5) Those that assess relational dimensions and overall satisfaction with sexual life, such as the Index of Sexual Satisfaction [27]; or the Satisfaction with Sex Life Scale [28], among others.…”
Section: Introductionmentioning
confidence: 99%
“…People with low sexual satisfaction are at greater risk of unsatisfactory relationships and marital problems compared to sexually satisfied individuals [5][6][7]. Likewise, men who were dissatisfied with their sex lives were more likely to pay for sex [8]. On the other hand, evidence indicates that sexual functioning [9], partner communication [10], marital satisfaction [5], sexual assertiveness [3], social support [11], marital intimacy [12], low religious beliefs [13], and good relationships with children and family are also associated with high levels of sexual satisfaction [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, some differences have been found between the two groups in terms of certain factors such as sexual behaviours and sexual aggression (Belza et al, 2008;Schei & Stigum, 2010;Shilo et al, 2021;Ward et al, 2005). Some studies have found a correlation between pornography consumption and paying for sex (Deogan et al, 2021;Farley et al, 2011;Shilo et al, 2021;Tewksbury & Golder, 2005;Wright, 2013;Wright & Randall, 2012). Another study, based on a sample from the US and the UK, found a correlation between purchasing sex and social attitudes.…”
Section: Understanding Individual Experiences Of Purchasing Sexmentioning
confidence: 99%